ANALYSIS OF FACTORS RELATED TO SAFE BEHAVIOR OF WORKERS (Cross-sectional Study: Construction Project Building X, Purwokerto) - Parmasari, Damairia Hayu; Suryanto; Rubai, Windri Lesmana; Isnubroto, Danang (The Indonesian Journal of Public Health, 2025)
Introduction: The work environment must prioritize the implementation of Occupational Safety and Health (OSH) measures to prevent accidents and work-related illnesses. A key aspect of Occupational Safety and Health implementation is the promotion of safe behavior among workers. This is particularly crucial in the construction sector, where workers are frequently exposed to high-risk conditions. According to the Indonesian Employment Social Security Administration, construction-related incidents accounted for the highest proportion of work accidents in 2023, contributing 32% of all reported cases. Building X in Purwokerto is one such construction project that is currently ongoing and subject to these occupational safety concerns. Aims: This research aims to determine the factors related to safe behavior in construction workers in Building X, Purwokerto. Methods: A cross-sectional design was applied, and the population included all construction workers in Building X, consisting of 89 workers. The independent variable measured is safe behavior, while the dependent variables include age, work experience, length of service, knowledge, attitudes, availability of Personal Protective Equipment (PPE), training, supervision, and regulations. The instrument used was a questionnaire containing questions about age, work experience, length of service, knowledge, attitudes, training, supervision, and regulations. Results: There is no significant correlation between age, length of service, work experience, knowledge, attitudes, training, and regulation and safe behavior with p-value >0.05. Conclusion: There is no significant correlation between age, length of service, work experience, knowledge, attitudes, training, and regulations and safe behavior among workers in Building X.